Improving Science Learning Achievement about Various Types of Objects Through Experimental Methods in Class IV Elementary School Students - Sutinah Sutinah (Eduvest - Journal of Universal Studies, 2023)
This research is a Classroom Action Research which was conducted in class IV of SD Negeri Setiadarma 04, Tambun Selatan District, Bekasi Regency. The purpose of the study is to improve science learning achievement about various forms of objects in grade IV students of SD Negeri Pondok Kacang Timur 03 Semester 1 of 2015/2016 through experimental methods.The use of the experimental model can improve student learning outcomes in science subjects, the subject of various material forms for class IV semester I, SD Negeri Setiadarma 04, Tambun Selatan District, Bekasi Regency, in the 2015/2016 academic year, this is indicated by an increase in learning outcomes, namely the learning process before the action shows low learning outcomes, namely students whose grades met the KKM as many as 13 students or 37%, students who had not completed 21 students or 61% with the highest score of 90 and the lowest score of 40. In cycle I the number of students who completed 21 students or 61% while those who had not completed 13 students or 39%. The minimum score is 50 and the maximum score is 90. In cycle II there is an increase in learning outcomes, namely the number of students' completeness is 32 students or 94%. Minimum score of 70 and maximum value of 100. Thus it can be concluded that using the experimental method can improve student learning outcomes in science subjects.